Bragg grating in a polymer optical fibre for strain, bend and temperature sensing - Kalli, Kyriacos; Zhang, Chi; Webb, David J.; Peng, Gangding; Chen, Xianfeng (My University, 2010)
We report on a Bragg grating written in an eccentric-cored polymer optical fibre for measurement of strain, bend and temperature. The strain sensitivity achieves 1.13 pm με -1. The temperature response shows a negative sign with the thermal sensitivity of -50.1 pm °C -1. For bend sensing, this device exhibits a strong fibre orientational dependence, wide bend curvature range of ±22.7 m -1 and a high bend sensitivity of 63.3 pm/m -1.
Keywords: Bragg gratings; Temperature; Optical fibers; Fiber optics